2014
DOI: 10.1001/jamaneurol.2014.65
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Circadian Rhythm Regulation in Early Parkinson Disease

Abstract: IMPORTANCE Sleep disturbances are recognized as a common nonmotor complaint in Parkinson disease but their etiology is poorly understood. OBJECTIVE To define the sleep and circadian phenotype of patients with early-stage Parkinson disease. DESIGN, SETTING, AND PARTICIPANTS Initial assessment of sleep characteristics in a large population-representative incident Parkinson disease cohort (N=239) at the University of Cambridge, England, followed by further comprehensive case-control sleep assessments in a sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
316
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 356 publications
(356 citation statements)
references
References 34 publications
11
316
0
8
Order By: Relevance
“…The analysis included two population‐based, incident cohort studies (Cambridgeshire Parkinson's Incidence from GP to Neurologist [CamPaIGN],17 Parkinsonism: Incidence, Cognition and Non‐motor heterogeneity in Cambridgeshire (PICNICS)14, 18; five purpose‐built biomarkers and clinical observational studies from academic centers (Harvard Biomarker Study [HBS],19, 20, 21, 22 PROfiling PARKinson's disease [PROPARK],16 and the French Drug Interaction with Genes in PD [DIGPD]); as well as two well‐phenotyped, failed phase III clinical trials with longitudinal, observational extension studies (Deprenyl and Tocopherol Antioxidative Therapy of Parkinsonism [DATATOP]15; Parkinson Research Examination of CEP‐1347 Trial/A Longitudinal Follow‐up of the PRECEPT Study Cohort [PreCEPT/PostCEPT]13. Six cohorts enrolled patients with a diagnosis of PD established according to modified UK PD Society Brain Bank diagnostic criteria.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis included two population‐based, incident cohort studies (Cambridgeshire Parkinson's Incidence from GP to Neurologist [CamPaIGN],17 Parkinsonism: Incidence, Cognition and Non‐motor heterogeneity in Cambridgeshire (PICNICS)14, 18; five purpose‐built biomarkers and clinical observational studies from academic centers (Harvard Biomarker Study [HBS],19, 20, 21, 22 PROfiling PARKinson's disease [PROPARK],16 and the French Drug Interaction with Genes in PD [DIGPD]); as well as two well‐phenotyped, failed phase III clinical trials with longitudinal, observational extension studies (Deprenyl and Tocopherol Antioxidative Therapy of Parkinsonism [DATATOP]15; Parkinson Research Examination of CEP‐1347 Trial/A Longitudinal Follow‐up of the PRECEPT Study Cohort [PreCEPT/PostCEPT]13. Six cohorts enrolled patients with a diagnosis of PD established according to modified UK PD Society Brain Bank diagnostic criteria.…”
Section: Methodsmentioning
confidence: 99%
“…The hypercortisolism has also been found in patients with earlystage PD. Breen et al reported that there was an elevated total serum cortisol level and half of the patients had arrhythmic cortisol profiles but with no phase shifting [74]. This phenomenon has also been verified with the saliva biopsy in PD patients.…”
Section: Cortisolmentioning
confidence: 81%
“…They showed reduced melatonin production with arrhythmic expression. In addition, the cortisol level is elevated and the brain and muscle arnt-like protein-1 (Bmal1) expression is altered in PD patients when compared with controls [74]. Further, the reduced melatonin output in PD patients is significantly related to the degeneration of hypothalamic gray matter and the disease severity [75].…”
Section: Melatoninmentioning
confidence: 99%
“…Повышенная дневная сонливость также может рассматривается в качестве премотор-ного маркера развития БП [17]. Ранние изменения циркадной регуляции сна, связанные с БП, могут предшествовать двигательным расстройствам [11].…”
Section: нарушения сна и бодрствования как маркер развития бпunclassified